Cryopreservation, early seedling development, and genetic stability of Oncidium flexuosum Sims - Galdiano Jr., Renato Fernandes [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP]; Vendrame, Wagner Aparecido (Springer Nature, 2013)
An efficient cryopreservation protocol was developed for mature seeds of Oncidium flexuosum Sims. Seed morphology, protocorm formation, and early seedling development were also assessed. The effects of phloroglucinol and Supercool X-1000® as cryoprotectant additives in the vitrification solution were investigated. Dehydration using the plant vitrification solution 2 (PVS2) for 60 and 120 min prior to immersion in liquid nitrogen promoted the highest frequency of in vitro seed germination 6 weeks following culture on half-strength Murashige and Skoog (1/2 MS) medium. Mature seeds submitted to vitrification for 120 min in PVS2 and 1 % phloroglucinol at 0 °C enhanced germination by 68 %, whereas in PVS2 and 1 % Supercool X-1000® germination was just moderately enhanced (26 %). In vitro-germinating seedlings developed healthy shoots and roots without the use of plant growth regulators. After 6 months of growth, there were no differences between in vitro- and ex vitro-grown seedlings for various phenotypic characteristics, including shoot length, number of leaves, number and length of roots, and fresh and dry weight. Seedlings were transferred to greenhouse conditions and successfully acclimatized, further developing into normal plants with over 90 % survival. Comparative analysis of seedlings from control and vitrified seeds using flow cytometry indicated that no change in ploidy levels occurred as a result of cryopreservation, therefore maintaining seedlings genetic stability. In this study, vitrification with PVS2 for 120 min with the addition of 1 % phloroglucinol offers a simple, safe, and feasible protocol for cryopreservation of O. flexuosum mature seeds. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Flow cytometry analysis; In vitro germination; Native orchid; Phenotypical characteristics; Vitrification; Comparative analysis; Greenhouse conditions; In-vitro; Plant growth regulators; Seedling development; Biological materials preservation; Cultivation; Flow cytometry; Liquid nitrogen; Plants (botany); Supercooling; Seed; Oncidium flexuosum; Orchidaceae